O nastanku in pomenu renskega tektonskega jarka in sosedstva - Kunaver, Jurij (Geografski obzornik, 1997)
The Rhine Rift valley shape is the result of the rifting which begins some 60 milion years ago. It is known as a hot spot due to the eruption of the hot mantle into the crust, which caused the crust uplift and the mantle overflow with the development of the Black Forest, the Vosges and the Rhine Rift valley. The region discussed is the most important European traffic corridor which has great economic potential.
Keywords: Francija; geografija; geotektonika; Nemčija; Ren; tektonski premiki